(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Computed tomography (CT) scan is widely used as a rapid and decisive diagnostic method. During CT examinations part of the radiation is scattered from the device. In normal practice, only patient will be allowed to presence inside CT room during examination. However, in some cases medical staff must remain in the CT room. This work aims to study the amount of scattering radiation during CT examinations at Al-Zahraa Hospital, Diyala, Iraq and assess the radiation impact on the thyroid gland hormones for radiation workers to evaluate the severity of the radiation exposure. All data were collected during the month of May to June, 2022. The results showed that the highest amount of scattered radiation was 18.55 mSv in front of the CT gantry head and the lowest scattered radiation was found at both sides of the CT scan device with values of 0.28 mSv and 0.27 mSv. The study also evaluated the impact of scattering radiation on the thyroid gland by testing the triiodothyronine and thyroxine hormones, together with the stimulation hormone in blood from 50 respondents of different gender, age and working time in the CT examination room. The test results showed that the probability of developing thyroid gland disorder increases for radiation workers in comparison to non-radiation workers. These effects were more severe for radiation workers with longer duration of work inside the ionizing radiation units. Thus, exposure to ionizing radiation increases the risk of developing a thyroid gland disorder for workers in CT scan unit.